Present Situation of Mongolian Development and its Future Prospects - Tsedendamba, L (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i13.13 Mongolian Journal of International Affairs No.13 2006 pp.109-118